2020
DOI: 10.1021/jasms.0c00258
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation by the Acidic Glycosidase PNGase H+ Enables Analysis of N-Linked Glycoproteins by Hydrogen/Deuterium Exchange Mass Spectrometry

Abstract: 1Hydrogen/deuterium exchange monitored by mass spectrometry (HDX-MS) has become an important method 2 to study the structural dynamics of proteins. However, glycoproteins represent a challenge to the traditional 3 HDX-MS workflow for determining the deuterium uptake of the protein segments that contain the glycan. We 4 have recently demonstrated the utility of the glycosidase PNGase A to enable HDX-MS analysis of N-glycosylated 5 protein regions. Here we have investigated the use of the acidic glycosidase PNGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…We have previously shown how microchips can be manufactured by simple and mild thiol−ene chemistry and how pepsin can be immobilized on such microchips via simple and mild thiol−ene "click chemistry" to create an IMER capable of efficient and online proteolysis of proteins in a bottom-up UPLC-MS workflow. 24 In a similar manner, PNGases A, H + , and Dj were immobilized onto thiol−ene microchips of a similar design to investigate the effect of immobilization on activity for each PNGase. PNGase IMERs were interfaced with a conventional UPLC-HDX-MS setup using in-house-manufactured three-dimensional (3D)-printed microchip holders (Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown how microchips can be manufactured by simple and mild thiol−ene chemistry and how pepsin can be immobilized on such microchips via simple and mild thiol−ene "click chemistry" to create an IMER capable of efficient and online proteolysis of proteins in a bottom-up UPLC-MS workflow. 24 In a similar manner, PNGases A, H + , and Dj were immobilized onto thiol−ene microchips of a similar design to investigate the effect of immobilization on activity for each PNGase. PNGase IMERs were interfaced with a conventional UPLC-HDX-MS setup using in-house-manufactured three-dimensional (3D)-printed microchip holders (Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 Furthermore, acetamido groups in glycan structures may retain significant amounts of deuterium under quench conditions, complicating the interpretation of glycopeptide HDX. 22 We have previously shown that in-solution deglycosylation at quench conditions with PNGase A and PNGase H + enables the study of the native conformational dynamics of glycoproteins like IgG1 antibodies or glycosylated serpins by HDX-MS. 23,24 The workflow has, however, three main limitations: (1) extensive manual sample handling is required potentially leading to low repeatability in HDX measurements, (2) large amounts of expensive or commercially inaccessible enzymes are consumed, and (3) the injection of high amounts of glycosidase into the system may lead to undesirable effects during LC−MS.…”
mentioning
confidence: 99%
“…Post-HDX deglycosylation optimization, sample preparation, and analysis were carried out similarly to that reported by the Rand group. , Briefly, after incubation with 90% v/v D 2 O/H 2 O (pD 7.4), CD16a was quenched with a pepsin-coupled beads slurry in a citric acid buffer, with 0.2 M TCEP (final pH 2.5), and incubated for 10 min at 11 °C for optimized digestion. The beads were removed by centrifugal filtration, and the resulting peptides deglycosylated with PNGase A for 4 min at 11 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Deglycosylation also risks destabilizing the proteins and can cause aggregation. PNGase A and PNGase H + are enzymes of choice when it is desirable to remove the N-linked glycosylations after labeling to preserve the native conformational dynamics and interaction of the glycoproteins (49,50). Nevertheless, these enzymes require offline pepsin digestion and manual sample injection into the LC-MS system, which can be more labor-intensive than the automated sample injection system conventionally employed in the epitope mapping experiment.…”
Section: Insufficient Sequence Coveragementioning
confidence: 99%